EXPLORING EDUCATION STUDENTS' PERCEPTIONS AND CHALLENGES IN UTILIZING ARTIFICIAL INTELLIGENCE FOR ACADEMIC PURPOSES - Rio Febrianto Arifendi; Riantina Fitra Aldya (Universitas Tribhuwana Tunggadewi, 2026)
This study aims to determine the student’s perceptions about their learning interest based on learning environment. Data collection using a survey with a population of all 207 students of Biology and Mathematics Education in year of 2022, 2023, 2024 and 2025 using stratified random sampling. This survey is related in two aspect of students perceptions about Artificial Intellligence (AI), which are: 1) students’ perceptions related of the use of AI in the learning processtheir learning interest with 5 indicators such as ease of using AI, benefits of AI in learning, the influence of AI on learning effectiveness, the impact of AI on critical thinking skills, and ethics of using AI in academics; 2) students' perceptions of ai impact for futher learning with 3 indicators such as aspects such as learning effectiveness, motivation and interest in learning, and independence and critical thinking. The results showed that the higher score in first aspect was related to the statement that AI makes task completion easier, with an average score of 4.45, categorized as Strongly Agree, and the lowest score are in second aspect related to increasing learning motivation obtained an average score of 3.08, categorized as Moderately Agree. So,it showed that AI has become an effective learning support tool in higher education, particularly in helping students obtain information efficiently, but it also indicate concerns regarding reduced critical thinking skills and the emergence of dependency on AI in completing academic tasks.